TUGAS POKOK OPERATOR FRONT OFFICE DEPARTMENT DI GRAND ROCKY HOTEL BUKITTINGGI - Widya Astuti; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to find out how the Main Duties of Front Office Department Operators at Grand Rocky Hotel Bukittinggi. This study discusses the main duties of a telephone operator, starting from what are the duties of a telephone operator in general at Grand Rocky Hotel Bukittinggi, SOPs in becoming a telephone operator and which are the main tasks of telephone operators, both handling telephone requests, handling telephone calls, and handling telephone calls. telephone calls, handling waking guests, handling music/radio/VCD programs and serving E-mail delivery. This study uses a qualitative method, where the data obtained through interviews, observation and documentation. The results of the research conducted at the Grand Rocky Hotel Bukittinggi are sufficient to meet the existing standards, there are only a few indicators that differ between the theory and the Grand Rocky Hotel Bukittinggi. Keywords: Implementation of basic tasks, telephone connection requests, handling telephone call connection fees, handling music/radio/VCD programs and serving E -mail delivery